Thwarted Belongingness Hindered Successful Aging in Chinese Older Adults: Roles of Positive Mental Health and Meaning in Life - Yu, Yongju (Frontiers in Psychology, 2022)
Aging of population has brought great challenges to many regions throughout the world. It has been demonstrated that interpersonal relationship is closely related to the experiences of aging for older adults. However, it still remains unknown how and under what conditions thwarted belongingness links to successful aging. This study examined the relationship between thwarted belongingness and successful aging and tested the mediating role of positive mental health and the moderating role of meaning in life. Community-dwelling older adults (n = 339) aged 60–75 years recruited in Chongqing, China completed self-measures of thwarted belongingness, successful aging, meaning in life, and positive mental health. Correlation analyses showed that successful aging was associated with less thwarted belongingness, better positive mental health, and higher levels of meaning in life. Positive mental health was found to totally mediate the negative effect of thwarted belongingness on successful aging. Moderated mediation analyses further revealed that two components of meaning in life (present of meaning and search for meaning) attenuated the indirect effect of thwarted belongingness on successful aging via positive mental health. This study highlights the protective roles of positive mental health and meaning in life and addressed cultural aspects in the process of successful aging among Chinese older adults.